2019
DOI: 10.17221/46/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of systemic lupus erythematosus in dogs with canine adipose-derived stem cells

Abstract: A 6-year-old, intact female, Maltese presented with limited movement of the hind limbs and intermittent pruritus for three months. The patient was diagnosed with systemic lupus erythematosus. Conventional immunosuppressive therapy was attempted for 70 days; however, the patient still suffered from life-threatening pancreatitis and hepatopathy. Therefore, we tried canine adipose-derived mesenchymal stem cells for immunomodulation and liver protection. After 6-months of the stem cell therapy, the patient’s walki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…According to Garden (2022), the use of MSCs, applied intravenously in immunomediated cytopenias (immunomediated hemolytic anemia and/or immunomediated thrombocytopenia) showed a positive result in 17 of the 22 dogs followed up. The study showed that, of the 17 patients with a positive response, 12 had a complete response, with or without the help of immunosuppressants, and 5 had clinical and cell number improvement, but with a cell count below normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Garden (2022), the use of MSCs, applied intravenously in immunomediated cytopenias (immunomediated hemolytic anemia and/or immunomediated thrombocytopenia) showed a positive result in 17 of the 22 dogs followed up. The study showed that, of the 17 patients with a positive response, 12 had a complete response, with or without the help of immunosuppressants, and 5 had clinical and cell number improvement, but with a cell count below normal.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive medications are the basis for the treatment of autoimmune diseases, but they can cause adverse effects in the patient. In other autoimmune diseases, such as systemic lupus erythematosus, in which the patient may suffer from several metabolic changes, the use of MSCs may be an option for the treatment of the disease (Ko, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Os sinais clínicos induzidos pelo LES não são patognomônicos da doença e, são dependentes dos órgãos afetados (ROSADO et al, 2021). Pele, articulações e rins são os órgãos mais acometidos, lesões dermatológicas com hematomas devido à trombocitopenia e hemólise imunomediada, insuficiência renal pela glomerulonefrite (KO et al, 2019) são os achados mais comuns. Entretanto, poliartrite, polimiosite, linfadenopatia, pericardite e pleurite também podem estar presentes (BRKLJACIC et al, 2017).…”
Section: Sinais Clínicosunclassified
“…Nesse contexto, os principais sinais clínicos e achados laboratoriais que podem ser visualizados em animais com lúpus eritematoso sistêmico são: poliartrite, polimiosite, lesões cutâneas, glomerulonefrite, anemia hemolítica, leucopenia e trombocitopenia (KO et al, 2019). Todos esses sinais clínicos e achados estão intimamente relacionados com as reações de hipersensibilidades dos tipos II, III e IV (TIZARD, 2019).…”
Section: Introductionunclassified